Pengaruh Beban Siklik Pada Tanah yang Distabilisasi Dengan Kapur Terhadap Nilai CBR - Arrazi, Shamer; Nurtjahjaningtyas, Indra; Wicaksono, Luthfi Amri (Department of Civil Engineering, Diponegoro University, 2025)
Roads built on soft clay soils will experience damage before the service life is complete. One of the most common damages is potholes. The cyclic load is the repetitive load caused by the wheels of a vehicle. Stabilization of the subgrade needs to be done to overcome this problem, namely by adding lime. The lime used is quicklime from Sampang, Madura. The research was conducted to obtain the optimum lime mixture in the soil. CBR test was conducted on the soil with 3%, 5%, and 7% lime mixture. After that, cyclic loading was applied to analyze its effect on the CBR value. The original soil had a CBR value of 11.36% which then decreased to 5.79% after cyclic loading. The CBR values of 3%, 5%, and 7% lime-stabilized soil were 31.96%, 35.22%, and 34.48%, respectively. The optimum lime mixture in this study is 7% with a CBR value of 34.48% and a decrease in CBR value due to cyclic loading to 30.74%. Stabilization with lime can increase the CBR value up to 5% lime mixture. The addition of excess lime will reduce the CBR value. In addition, the decrease in CBR value due to cyclic loading decreases with the addition of lime. This is because the absorption and flocculation reactions by lime cause changes in the distribution of soil grain gradation.